Genetic diversity in cocoa germplasm of southern Cameroon revealed by simple sequences repeat (SSRS) markers - Efombagn, M.I.B.; Sounigo, O.; Nyassé, S.; Dauleux, M.M.; Cilas, Christian; Eskes, M.A.; Allen, K. (2006)
The range of polymorphism of about 194 cocoa accessions collected in farms in Southern Cameroon during field surveys and 71 Trinitario and Upper Amazon clones available in genebanks on-station was assessed using 13 SSR markers. The gene diversity, genetic differentiation and genetic similarities were analysed for the different populations. In total, 282 alleles were detected within all the populations studied. The farm accessions were strongly differentiated based on their geographical origin, with accessions coming from the East province clustering together with local Trinitario accessions from the genebank. Accessions from the Centre-South provinces clustered with Amazon and hybrid accessions, suggesting more uptake of seed garden materials in farms in these provinces. The genetic diversity parameters indicate that the farmers’ planting material is not highly diverse, and is genetically close to parental genotypes available in genebanks. However, some promising Upper Amazon clones (T-clones) that have also been used as parents of released hybrid varieties were genetically distant from the accessions. This result suggests that the progenies of these parents have so far been poorly used in the cocoa farms surveyed. The consequences of these findings for cocoa breeding in Cameroon are discussed.